Which Board Interlocks Matter? The Impact of Managerial Power, Legitimacy, and Family Power on the Adoption of Stock Option Pay - Yoshikawa, Toru (Institutional Knowledge at Singapore Management University, 2013)
Inter-organizational relationships and the networks they create are an important mechanism for the transfer of knowledge and learning. Network ties enable the transfer of experiential knowledge – for instance of vicarious information through board interlocks. While we know that organizational learning occurs and is influenced by factors like the strength of ties and a firm’s position in the network, it is still unclear what causes the firm to act on the information gained through network ties. We build on prior studies on the impact of interlocking board ties ion the adoption of new practices and analyze the effects of different types of board ties on the adoption of a new practice that has yet to gain strong legitimacy in the institutional field. To study differences in the motivation and power of those who create inter-firm ties, we focus on the role of board interlocks in the adoption of stock option pay among Japanese firms. We investigate whether the effects of interlocks on the adoption of this new practice differs for sent ties – established when an executive of the focal firm serves on another firm’s board – and for received ties that are created when an executive of another firm sits on the focal firm’s board. We theorize that the observed effects vary by the type of tie that links the focal firm with a prior adopter. Executives of the focal firm who serve on the board of a prior adopter have managerial power to act on the information they obtained because they are in a position to make key decisions, while executives of a prior adopter who serve as outside directors on the board of the focal firm generally lack respective managerial power and hence only indirectly influence managerial decisions. When an executive has the motivation to adopt a new practice, for example to gain personal benefits, then this power difference will likely have even a greater impact on the adoption decision. Our findings show that sent ties are significantly related to the adoption of stock option pay whereas received ties are not, thus confirming our argument that managerial power and motivation of those who transfer information matter. The effects of sent ties are further strengthened by large foreign ownership and high levels of industry diffusion suggesting their complementary effects on managerial power. We also find that family ownership positively affects the impact of ties on the adoption of stock option pay. These findings suggest that information is not sufficient for the new practice to be adopted but that managerial and family power is important in the adoption decision.